Pathways as "signatures in landscape": towards an ethnography of mobility among the Mbya-Guaraní (Northeastern Argentina) - Crivos, Marta (2007)
Processes of spatial mobility among the Mbya are of interest in anthropological and ethnobiological studies, as these processes are related to transformations in the landscape and the environment. Despite this, ethnographic literature usually focuses itself on the mobility of Guaraní communities from the perspective of population dynamics on a regional scale. Our research among two Mbya-Guaraní communities in the Argentinean province of Misiones has enabled us to recognize patterns of mobility on a micro-scale. Certainly, the mobility of adult members of these communities as they perform hunting and gathering activities delimit spaces of individual use. We consider the different pathways as "signatures in landscape", resulting from processes of spatial mobility inherent to those activities Taking into account the gathering and circulation of medicinal plants for treatment of gastrointestinal illnesses, we have been able to identify different pathways inherent in their search, towards the monte or other spaces away from de settlement. The design and construction of the pathways is determined by the specific personal knowledge of individuals who search for these valuable resources. Using both strategies of direct observation - as members of the community manipulate different resources during these search and gathering trips - and interviews, we have been able to gather and interpret significant information on the strategies used by the Mbya to domesticate the monte areas. As a consequence of our approach we suggest that the landscape design resulting from these trips should not be considered a consensual or collective strategy of the whole community; it is rather the result of the daily strategies of individuals, which involves the selection of resources mainly based on each individual's knowledge and interests.